$L^p-L^q$ estimates for non-local heat and wave type equations on locally compact groups - Gómez Cobos, Santiago; Restrepo, Joel E.; Ruzhansky, Michael (Comptes Rendus. Mathématique)
We prove the $L^p-L^q$ $(1